2018
DOI: 10.1002/anie.201812937
|View full text |Cite
|
Sign up to set email alerts
|

Access to N‐Substituted 2‐Pyridones by Catalytic Intermolecular Dearomatization and 1,4‐Acyl Transfer

Abstract: A novel rhodium‐catalyzed dearomatization of O‐substituted pyridines to access N‐substituted 2‐pyridones has been developed. A computational study suggests a mechanism involving the formation of a pyridinium ylide followed by an unprecedented 1,4‐acyl migratory rearrangement from O to C. Furthermore, the chiral dirhodium complexes serve as the catalyst for the asymmetric transformation with excellent enantioselective control. DFT calculations indicate the chirality is transferred from axial chirality to the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…3 and 4 for more details). Furthermore, this calculation demonstrated that this [1,4]-acyl migration presumably proceeds via a free ylide intermediate, which was consistent with the known [1,4]-acyl migration from O to C 64 .…”
Section: Resultssupporting
confidence: 83%
“…3 and 4 for more details). Furthermore, this calculation demonstrated that this [1,4]-acyl migration presumably proceeds via a free ylide intermediate, which was consistent with the known [1,4]-acyl migration from O to C 64 .…”
Section: Resultssupporting
confidence: 83%
“…Metal‐carbene mediated alkylation of 2‐pyridones with diazo compounds appears to favor O−H over N−H insertion [3] . To finesse this limitation, we have developed an enantioselective, rhodium‐catalyzed dearomative N‐alkylation of 2‐oxypyridines involving ylide formation and O‐to‐N acyl rearrangement [4] . However, this protocol was also limited in its requirement for donor–acceptor diazoacetates as the alkylation reagents.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike 2‐oxypyridines which react with Rh‐carbene only at its N‐site, [4] 2‐pyridone is a more challenging substrate. As shown in Scheme 4 and Figure S1, 2‐pyridone ( Pyr O‐NH ) is more stable than its isomer 2‐hydroxypyridine ( Pyr N‐OH ) and its isomerization is feasible.…”
Section: Methodsmentioning
confidence: 99%